Socioeconomic and Racial Disparities and Survival of Human Papillomavirus–Associated Oropharyngeal Squamous Cell Carcinoma. (January 2021) - Rotsides, Janine M.; Oliver, Jamie R.; Moses, Lindsey E.; Tam, Moses; Li, Zujun; Schreiber, David; Jacobson, Adam S.; Hu, Kenneth S.; Givi, Babak
Objective: To investigate differences in epidemiology of oropharyngeal squamous cell carcinoma (OPSCC) with regards to human papillomavirus (HPV), race, and socioeconomic status (SES) using the National Cancer Database (NCDB). Study Design: Population-based cohort study. Setting: Racial and socioeconomic disparities in survival of OPSCC have been previously acknowledged. However, the distribution of HPV-related cancers and its influence on survival in conjunction with race and SES remain unclear. Subjects and Methods: All patients with OPSCC in the NCDB with known HPV status from 2010 to 2016 were included. Differences in presentation, HPV status, treatment, and outcomes were compared along racial and socioeconomic lines. Univariable and multivariable Cox regression survival analyses were performed. Results: In total, 45, 940 patients met criteria. Most were male (38, 038, 82.8%), older than 60 years (23, 456, 51.5%), and white (40, 156, 87.4%), and lived in higher median income areas (>48, 000, 28, 587, 62.2%). Two-thirds were HPV positive (31, 007, 67.5%). HPV-negative disease was significantly more common in lower SES (<38, 000, 2937, 41.5%, P < .001) and among blacks (1784, 55.3%, P < .001). Median follow-up was 33 months. Five-year overall survival was 81.3% (95% CI, 80.5%-82.1%) and 59.6% (95% CI, 58.2%-61.0%) in HPV-positive and HPV-negative groups, respectively. In univariable and multivariable analyses controlling for HPV status, age, stage, and treatment, black race (hazard ratio [HR], 1.22; 95% CI, 1.11-1.34; P < .001) and low SES (HR, 1.58; 95% CI, 1.45-1.72; P < .001) were associated with worse survival. Conclusion: Significant differences in HPV status exist between socioeconomic and racial groups, with HPV-negative disease more common among blacks and lower SES. When controlling for HPV status, race and SES still influence outcomes in oropharyngeal cancers.